ANALISIS PERTUMBUHAN EKONOMI INKLUSIF KABUPATEN/KOTA DI PROVINSI JAWA TENGAH - Wulan Retno Hapsari (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2019)
In essence, economic development is a series of businesses and policies aimed at improving the standard of living of the community, expanding employment, equalizing the distribution of people’s income, increasing regional economic relations and through shifting economic activities from the primary sector to the secondary and tertiary sectors. In other words, the direction of economic development is to ensure that people's income rises and accompanied by the best level of equity possible. In the perspective of measuring the quality of economic growth, in addition to looking at the achievements of economic and social indicators in the discussion above, a measure of the quality of economic growth can be seen from the Inclusive Growth Index (IGI). IGI of Regency/City in Central Java province shows there are 6 Regencies/Cities that are in the very satisfactory category, 25 Regencies/Cities that are in the satisfactory category and there are 4 Regencies in the unsatisfactory category.